Horses discriminate between human facial and vocal expressions of sadness and joy - Jardat Plotine; Liehrmann Océane; Reigner Fabrice; Parias Céline; Calandreau Ludovic; Lansade Léa (SPRINGER HEIDELBERG, 2025)
Communication of emotions plays a key role in intraspecific social interactions and likely in interspecific interactions. Several studies have shown that animals perceive human joy and anger, but few studies have examined other human emotions, such as sadness. In this study, we conducted a cross-modal experiment, in which we showed 28 horses two soundless videos simultaneously, one showing a sad, and one a joyful human face. These were accompanied by either a sad or joyful voice. The number of horses whose first look to the video that was incongruent with the voice was longer than their first look to the congruent video was higher than chance, suggesting that horses could form cross-modal representations of human joy and sadness. Moreover, horses were more attentive to the videos of joy and looked at them for longer, more frequently, and more rapidly than the videos of sadness. Their heart rates tended to increase when they heard joy and to decrease when they heard sadness. These results show that horses are able to discriminate facial and vocal expressions of joy and sadness and may form cross-modal representations of these emotions; they also are more attracted to joyful faces than to sad faces and seem to be more aroused by a joyful voice than a sad voice. Further studies are needed to better understand how horses perceive the range of human emotions, and we propose that future experiments include neutral stimuli as well as emotions with different arousal levels but a same valence.